PERAN SOSIAL-EDUKASI PROFESI GURU DALAM MEMBANGUN HARMONI DI SEKOLAH - Muhammad Ibnu Athoillah (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2024)
Teachers have a central role in determining the success of the educational process. It is not surprising that every educational innovation effort, especially those related to curriculum changes and the development of human resource quality, is highly dependent on the existence and role of teachers. In carrying out their duties, teachers are required to play various roles and have the skills and responsibilities to create an active, creative, effective, and enjoyable learning process. This study uses a literature study approach. In socio-educational terms, teachers not only play a role in improving students' academic achievement, but also in shaping character and creating a harmonious and civilized school culture.